Jabotinsky's Children : Polish Jews and the Rise of Right-Wing Zionism - Heller, Daniel Kupfert (Book collections on Project MUSE., 2017)
How interwar Poland and its Jewish youth were instrumental in shaping the ideology of right-wing ZionismBy the late 1930s, as many as fifty thousand Polish Jews belonged to Betar, a youth movement known for its support of Vladimir Jabotinsky, the founder of right-wing Zionism. Poland was not only home to Jabotinsky's largest following. The country also served as an inspiration and incubator for the development of right-wing Zionist ideas. Jabotinsky's Children draws on a wealth of rare archival material to uncover how the young people in Betar were instrumental in shaping right-wing Zionist attitudes about the roles that authoritarianism and military force could play in the quest to build and maintain a Jewish state. Recovering the voices of ordinary Betar members through their letters, diaries, and autobiographies, Jabotinsky's Children paints a vivid portrait of young Polish Jews and their turbulent lives on the eve of the Holocaust. Rather than define Jabotinsky as a firebrand fascist or steadfast democrat, the book instead reveals how he deliberately delivered multiple and contradictory messages to his young followers, leaving it to them to interpret him as they saw fit. Tracing Betar's surprising relationship with interwar Poland's authoritarian government, Jabotinsky's Children overturns popular misconceptions about Polish-Jewish relations between the two world wars and captures the fervent efforts of Poland's Jewish youth to determine, on their own terms, who they were, where they belonged, and what their future held in store. Shedding critical light on a vital yet neglected chapter in the history of Zionism, Jabotinsky's Children provides invaluable perspective on the origins of right-wing Zionist beliefs and their enduring allure in Israel today.